Emotional behavioral outcomes of children with unilateral and mild hearing loss - Ong, Jun Jean; Smith, Libby; Shepherd, Daisy A.; Xu, Jessica; Roberts, Gehan; Sung, Valerie (Frontiers in Pediatrics, 2023)
Background: Deaf and hard-of hearing (DHH) children often experience emotional/behavioral difficulties. The impact of unilateral/mild hearing loss (HL) on children’s emotion and behavior are unclear. We aimed to describe emotional/behavioral, health related quality-of-life (HRQoL) and parent psychological distress outcomes of school-age children with unilateral/mild HL, compared to children with moderate to profound HL, and in relation to population norms; and identify predictive factors of emotional/behavioral difficulties. Methods: Data of 339 DHH children, 5-12 years, enrolled in the Victorian Childhood Hearing Longitudinal Databank (VicCHILD), which include demographics, early development, medical/audiological characteristics and parent rated questionnaires of emotion/behavior, HRQoL and parental psychological distress collected at various stages of child’s life were analyzed. We used Cohen’s d to investigate the outcomes by measuring the mean score differences of both groups with published norms and logistic regression to analyze the factors predictive of emotional/behavioral difficulties. Results: The proportion of children with unilateral/mild HL and moderate to profound HL who experienced emotional/behavioral difficulties was similar (18.3% vs 20.6%), with hyperactivity and poor prosocial behavior reported as the predominant symptoms in both groups. Mean emotional/behavioral scores of both groups were comparable and substantially higher than normative population scores. This was also the case for HRQoL and levels of parent distress. Among children with unilateral/mild HL, additional health needs were the strongest predictive factor, demonstrating an approximately 1.7-fold increase in odds of emotional/behavioral difficulties (OR=1.67; 95% CI 1.29-2.17, p<0.001) with every additional health need. Early developmental concerns, other than communication milestone and attending mainstream school showed weaker evidence of association. Conclusion: Children with unilateral/mild HL were just as likely as those with moderate to profound HL to experience more emotional/behavioral difficulties, poorer HRQoL and higher parental distress scores compared to population norms. Our findings justify the provision of early intervention, support and medical services for all DHH children to identify those at risk of poorer outcomes.